IMPLEMENTASI PERATURAN BUPATI SRAGEN NOMOR 11 TAHUN 2020 TENTANG PENERIMAAN PESERTA DIDIK BARU PADA TAMAN KANAK-KANAK, SEKOLAH DASAR DAN SEKOLAH MENENGAH PERTAMA TAHUN 2020/2021 - Sukisno . (Master of Public Administration, Universitas Slamet Riyadi, 2022)
The problem of New Student Admission (PPDB) is an annual problem that always arises at the beginning of each new school year. With the emergenceof the Regulation of the Minister of Education and Culture of the Republic ofIndonesia Number 44 of 2019, which regulates the implementation of the zoningbasedPPDBin2020,itbecomesthebasisfortheSragenRegencyGovernmentto implementandadaptittoregionalconditions.Asafollow-up,theSragenRegency GovernmentissuedRegentRegulationNo.11of2020asabasisandtheHeadof the Education and Culture Office issued a technical guideline as a technicalguideline for implementing PPDB in 2020. With preparation of regulations andadequate resources. PPDB 2020 in Sragen Regency can run smoothly. Keywords: The implementation; Sragen Regent's Regulation; Admission of NewStudents; the Edward III model. Succes of imlplementation.